Pivotal Clinical Study to Evaluate the Safety and Effectiveness of the MANTA Percutaneous Vascular Closure Device: The SAFE MANTA Study. (July 2019) - Wood, David A.; Krajcer, Zvonimir; Sathananthan, Janarthanan; Strickman, Neil; Metzger, Chris; Fearon, William; Aziz, Mark; Satler, Lowell F.; Waksman, Ron; Eng, Marvin; Kapadia, Samir; Greenbaum, Adam; et al.
Abstract : Background: Open surgical closure and small-bore suture-based preclosure devices have limitations when used for transcatheter aortic valve replacement, percutaneous endovascular abdominal aortic aneurysm repair, or percutaneous thoracic endovascular aortic aneurysm repair. The MANTA vascular closure device is a novel collagen-based technology designed to close large bore arteriotomies created by devices with an outer diameter ranging from 12F to 25F. In this study, we determined the safety and effectiveness of the MANTA vascular closure device. Methods and Results: A prospective, single arm, multicenter investigation in patients undergoing transcatheter aortic valve replacement, percutaneous endovascular abdominal aortic aneurysm repair, or thoracic endovascular aortic aneurysm repair at 20 sites in North America. The primary outcome was time to hemostasis. The primary safety outcomes were accessed site-related vascular injury or bleeding complications. A total of 341 patients, 78 roll-in, and 263 in the primary analysis cohort, were entered in the study between November 2016 and September 2017. For the primary analysis cohort, transcatheter aortic valve replacement was performed in 210 (79.8%), and percutaneous endovascular abdominal aortic aneurysm repair or thoracic endovascular aortic aneurysm repair was performed in 53 (20.2%). The 14F MANTA was used in 42 cases (16%), and the 18F was used in 221 cases(84%). The mean effective sheath outer diameter was 22F (7.3 mm). The mean time to hemostasis was 65±157 seconds with a median time to hemostasis of 24 seconds. Technical success was achieved in 257 (97.7%) patients, and a single device was deployed in 262 (99.6%) of cases. Valve Academic Research Consortium-2 major vascular complications occurred in 11 (4.2%) cases: 4 received a covered stent (1.5%), 3 had access site bleeding (1.1%), 2 underwent surgical repair (0.8%), and 2 underwent balloon inflation (0.8%). Conclusions: In a selected population, this study demonstrated that the MANTA percutaneous vascular closure device can safely and effectively close large bore arteriotomies created by current generation transcatheter aortic valve replacement, percutaneous endovascular abdominal aortic aneurysm repair, and thoracic endovascular aortic aneurysm repair devices. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02908880.